Studying and Learning Islam in Achieving Amal during Ramadan in the Community of Dusun Suka Makmur, Riau - Muya Syaroh Iwanda Lubis; Aldila Fadhlika; Khadijah Nadhirah Siregar; Miftahul Jannah; Nur Azlin Karimah; Sinta Aqila Istikomah; Suci Meilani S (As-sunnah: Jurnal Pengabdian Masyarakat, 2024)
The prosperous villagers were in the new village of rambah, kec. Rambah samo, kab. Tip upstream, prov. Riau is a society that has a strong desire to seek knowledge. The reasons for this desire are based on a society that has also begun to understand the Koran, the doctrine of Islam. Unfortunately, people's desires cannot be well expressed because there are some factors that cause them to be irresoluble and running. The lack of manpower and a da 'i in the village is one reason, not to mention a female daiyah or teacher. It is also felt by the taqwa mosque -- the people at the taqwa mosque -- have lost the will to learn because there is neither thrusters nor teachers. For women, there are no da 'iyah women salhaj salaf places to consult on the problems of women, to make women in these villages feel troubled, while women and children are desperately in need, their need for daiyah is so well described by the still many instances of misreading the Koran, still mistaking in worship (especially those that are included in the harmony of Islam), And the lack of understanding of women to the laws that pertain to women. The methods of this study use community based research (CBR), the findings of scientific research activities conducted have encouraged and given children and mothers the opportunity to be active and involved in increasing their love of the quran, Arabic and islamic language more deeply into women's fiqh laws during Ramadan.